Assessment of patient satisfaction in a tertiary and secondary hospitals of east Godavari district: a comparative study - Moses, Pidakala Mary; Babu, G. Krishna; Prasad, K. V. S.; Nadipena, Jhansi (International Journal Of Community Medicine And Public Health, 2020)
Background: Satisfaction is an important element in the evaluation of services rendered by a hospital. Patient satisfaction is as important as other clinical health measures and is a primary means of measuring the effectiveness of health care delivery. It refers to the patient’s state of being adequately rewarded. Patient satisfaction is a measure of success of the services being provided by the hospitals. Objective of the study was to assess the satisfaction levels of the people utilizing various services provided in secondary and tertiary health care delivery settings. Methods: Observational hospital based comparative study conducted among Inpatients aged 18 yrs and above from different wards who are discharged during the study period and are willing to participate in the study at Secondary and tertiary health care centres of East Godavari District during May 2015 to April 2016. Sample size was calculated using n-master version 2.0. Sample size calculation was based on assumption that the prevalence of patient satisfaction as 50% with mean difference of satisfaction of 15%, confidence interval of 95%, α - error of 5%, power 90%, with effect size 0.3, sample size estimated was 234 in each setting resulting in a cumulative sample size of 702. Results: It was found that 64.52% of inpatients of District Hospital, Rajahmundry, have expressed neutrality or dissatisfaction regarding overall admission services as compared to 49.14% in Government General Hospital, Kakinada and 14.52% in Area Hospital, Rampachodavaram. Conclusions: The overall patient satisfaction was observed to be around 80% for all the three hospitals.